Fractional Ablative Laser Therapy is an Effective Treatment for Hypertrophic Burn Scars: A Prospective Study of Objective and Subjective Outcomes. Issue 6 (December 2021) - Miletta, Nathanial; Siwy, Katherine; Hivnor, Chad; Clark, Jason; Shofner, Joshua; Zurakowski, David; Anderson, R. Rox; Lee, Kachiu; Donelan, Matthias
Abstract : Objective: The aim of this study is to determine objective and subjective changes in mature hypertrophic burn scars treated with a fractional ablative carbon dioxide (CO2 ) laser. Background: Fractional CO2 laser treatment has been reported to improve burn scars, with increasing clinical use despite a paucity of controlled, prospective clinical studies using objective measures of improvement. Methods: A multicenter, site-controlled, prospective open-label study was conducted from 2013 to 2016. Objective and patient-reported outcome measures were documented at baseline, at each monthly laser treatment, and 6 months after treatment. Objective measurements employed were: mechanical skin torque to measure viscoelastic properties; ultrasonic imaging to measure scar thickness; and reflectometry to measure erythema and pigmentation. Subjective measures included health-related quality of life, patient and investigator scar assessment scales, and blinded scoring of before and after photographs. Subjects aged 11 years or older with hypertrophic burn scars were recruited. Each subject received 3 monthly treatment sessions with an ablative fractionated CO2 laser. Results: Twenty-nine subjects were enrolled, of whom 26 received at least 1 fractional CO2 laser treatment and 22 received 3 treatments. Mean age of those completing all 3 treatments was 28 years. Statistically significant objective improvements in elastic stretch ( P < 0.01), elastic recovery ( P < 0.01), extensibility ( P < 0.01), and thickness ( P < 0.01) were noted. Patient- and physician-reported scar appearance and pain/pruritus were significantly improved ( P < 0.01). There was no regression of improvement for at least 6 months after treatment. Conclusions: Fractional ablative laser treatment provides significant, sustained improvement of elasticity, thickness, appearance, and symptoms of mature hypertrophic burn scars.